Beyond deviant damsels re-evaluating female criminality in the nineteenth century - Kilday, Anne-Marie 1971-; Nash, David 1960- (Oxford University Press, 2023)
This volume offers a new interpretation of women's criminality in the nineteenth century, countering assumptions that women commit crime in highly gendered ways and questioning the value of using stereotypes to analyse criminality, an approach that marginalises the importance of circumstances and individual choice